Multibeam bathymetry raw data (Kongsberg EM 122 working area dataset) of RV SONNE during cruise SO265 - Jörg Geldmacher; Reinhard Werner; Anne-Cathrin Wölfl (PANGAEA, 2021)
RV SONNE expedition SO265 was the central activity of the research project Shatsky Evolution that was funded by the German Federal Ministry of Education and Research and was conducted from 2018-08-26 and 2018-10-11 by the GEOMAR Helmholtz Centre for Ocean Research Kiel in collaboration with international partners (Geldmacher et al., 2018, GEOMAR Report 47, doi: 10.3289/GEOMAR_rep_ns_47_2018). The goal of the project was the investigation of the late stage evolution of Shatsky Rise, a vast, submarine volcanic plateau in the northwest Pacific. In particular, the project aimed to study the transition from plateau volcanism (the main body of Shatsky Rise) to postulated hotspot track volcanism (Papanin Ridge and/or Ojin Rise seamounts). Obtained bathymetric data were acquired by the ships own EM 122 multibeam system. A sound velocity profile (SVP) was applied on the data for calibration. SVP data are part of this dataset publication.